Women and work : changing scenario in India - Sharma, Alakh N.; Singh, Seema; Indian Society of Labour economics (Patna : Indian Society of Labour economics, 1992)
Selected articles, previously published in the Indian journal of labour economics
Includes bibliographical references
Keywords: Women -- India; Women -- Employment -- India; Sex discrimination in employment -- India